The integration of regional or minority languages in the European higher education area : Galician as a case study - Suarez Castiñeira, María Luz (Serie Letras (Bilbao, Spain), 2011)
"The Integration of Regional or Minority Languages in the European Higher Education Area. Galician as a Case Study presents an in-depth analysis of the data received in response to a questionnaire sent to higher education institutions across Europe, with provision including Galician language and culture. This study is indicative of the changes affecting the teaching of regional or minority languages at university level as a result of the process of convergence of higher education systems in Europe" (editor).